Tailored therapy for Helicobacter pylori eradication: A systematic review and meta-analysis - Qin Ma; Hancong Li; Jing Liao; Jing Liao; Zhaolun Cai; Bo Zhang (Frontiers Media S.A., 2022)
Background: Due to an increase in drug resistance, the eradication rate of H. pylori with empirical therapy has declined. Tailored therapy has been proposed as an alternative to standard empirical treatments. The necessity of personalized eradication therapy remains unclear. The aim of this study was to determine whether tailored therapy is superior to empirical therapy for H. pylori infection.Methods: We searched for eligible randomized controlled trials in the PubMed, Embase (Ovid), Wanfang, and Cochrane Central Register of Controlled Trials databases up to 10 December 2021. A random effects model comparing pooled relative risks (RRs) with 95% confidence intervals (CIs) was applied in the meta-analysis.Results: Twenty-one studies were included in the meta-analysis. In the first-line treatment, tailored therapy was more effective than empirical therapy (RR, 1.14 [95% CI, 1.08-1.21], I2 = 72.2%). In the second-line therapy setting, the results did not reveal significant differences between the two treatments (RR, 1.05 [95% CI, 0.84-1.30], I2 = 80.6%). A similar result was observed in mixed second- and third-line treatments (RR, 1.03 [95% CI, 0.96-1.11], I2 = 0.0%). Regarding adverse events, no significant differences were found between the two treatments (RR, 0.90 [95% CI, 0.80-1.01], I2 = 35.7%). Most of the results were highly heterogeneous.Conclusion: A tailored approach might provide a better eradication rate than empirical methods in first-line treatment. There might be no obvious advantage in second-line or mixed second- and third-line treatments third-line treatment. Due to the high heterogeneity, the results should be interpreted with caution. Further clinical studies are needed and justified.